Studi Banjir Kota Sungai Penuh di DAS Batang Merao (Studi Kasus: Kecamatan Hamparan Rawang) - Ary Firmana; Eka Oktariyanto Nugroho; Aziz Rizal Prasetiyo; Maulya Wijayanthi Sulistiyani; Adhyatma Taufik Akbar (The University of Lampung, 2026)
In January 2024, a major flood from Batang Merao River occurred in Sungai Penuh City, submerging residential areas and agricultural land to a depth of 0.5–1.5 m. One of the most severely impacted areas was Hamparan Rawang District with a total of 3985 houses and 866.025 ha of agricultural land inundated. This research aims to identify effective flood management alternatives to reduce inundation area and mitigate flood losses. The research was carried out through hydrological analysis, hydraulic analysis using HEC-RAS, and loss analysis using the ECLAC (Economic Commission for Latin America and the Caribbean) method. The study found that with Q25 discharges of 48.34 m³/s upstream and 720.62 m³/s downstream, an existing inundation area of 968.64 ha occurred, resulting in total losses of IDR 95.239 billion. Therefore, two flood management scenarios were developed, scenario 1 (river normalization) and scenario 2 (combination of river normalization and retention pond). Modeling results showed the inundation area under scenario 1 was 802.78 ha, reduce losses to IDR 43.604 billion (45.78% reduction). Under scenario 2, the inundation area was 780.51 ha, reduce losses to IDR 42,001 billion (44.10% reduction). Scenario 2 is effective for reducing inundation area, but for reducing financial losses, scenario 1 is more effective.